Les colonies latines et les frontières régionales de l’Italie - Olivier de Cazanove (Mélanges de la Casa de Velázquez)
Despite their artificial origin, the Augustan regions generally coincide with the pre-existing ethnic blocs. This article inquires into the way in which the regional boundaries were established, based on what references and what facts. The testimony of Horace (Satires, II, 1, 34-39), a native of the Latin colony of Venusia, reveals the notion of ethnic frontiers that prevailed in Italy between the Social War and the Augustan era. Venusia is a buffer zone between Apulia and Lucania and helps define the boundaries of the latter two. Far from being exclusive to Venusia, such an inter-border situation was a distinctive feature of all Latin colonies lying within the bounds (terrestrial or maritime) of the future Italian regions and founded later than 312 BC. Conceived as advance outposts of the empire of Rome, they also helped to fix ethnic boundaries between which the foreign body of Latinitas was introduced.